Statistical research development of neural networks and their role in the field of video production - A. A. Kostoglotov; G. G. Mikhailov; M. Yu. Napalkin (Современная наука и инновации)
The development of technology these days is amazing in its rapidity. Computer and network technologies have come a long way from local file sharing services to a global repository that absorbs the knowledge of many generations of humanity. However, now a new milestone in technology development is gaining momentum - artificial neural networks, which are something different than the prototypes of artificial intelligence shown to us in popular culture - films, TV series and books. These are assistants that are developing every day, capable of performing a wide range of tasks assigned by a person. Neural networks are becoming more and more rooted in our lives, and we use them without even realizing that they are branches of artificial intelligence. The list of them is quite large, starting from voice assistants aimed at quickly searching for information on the Internet. Due to competition in the technology market, almost every large IT company owns its own voice assistant, which is distributed on devices produced by the companies - personal computers, mobile phones and other smart devices. Among the most influential, it is worth noting the voice assistants ―Alice‖, developed by Yandex, ―Cortana‖ - developed by Microsoft, and ―Siri‖ - a voice assistant for devices created by Apple. Also, in addition to voice assistants that recognize voice commands, there are neural network generators that have found their niche in various branches of modern Internet media, from generating text to creating original images based on user requests. Video content is one of the fundamental pillars of media culture around the world and to this day, the majority of the population finds it preferable due to receiving more information in less time. However, now in view of the development of neural network technologies, the question arises: will actively learning neural networks replace full-fledged video production workers? The article will conduct a study of statistics on the use of neural networks for working with media content, and will also answer the question posed above.